Perang Komentar dan Kekerasan Simbolik di Era Digital: : Formulasi Teologi Perdamaian sebagai Kerangka Etis dalam Pendidikan Agama Kristen Kontekstual - Sumual, Elisa Nimbo; Arifianto, Yonatan Alex; Rahayu, Yohana Fajar (ELEOS: Jurnal Teologi dan Pendidikan Agama Kristen, 2025)
Abstract: The development of digital technology has created new social spaces that not only expand access to communication but also give rise to a form of non-physical violence known as symbolic violence. In this context, comment wars on social media have become one of the manifestations of digital conflict, characterised by hate speech, stigmatisation, and polarisation of opinions. Unfortunately, this symbolic violence has received little attention in theological discourse or contemporary Christian religious education. The increasing phenomenon of digital verbal conflicts among students and religious communities indicates an ethical void that requires a theological and educational response. This study aims to formulate and examine a theology of peace that can be integrated into Christian religious education. Using a descriptive qualitative method with a social media analysis approach and literature review, it can be concluded that the paradigm related to the nature of symbolic violence in digital comment wars is important. So that the principles of peace theology in biblical values can be actualised in Christian Religious Education as an instrument of digital peace ethics. And, of course, as a formulation of an ethical framework for peace theology in the context of digital Christian education. Christian religious education has strategic potential as a means of character formation for peace in the digital age. Thus, this ethical framework is expected to strengthen the role of the church and school in creating a fair and humane digital culture. Abstrak: Perkembangan teknologi digital telah menciptakan ruang sosial baru yang tidak hanya memperluas akses komunikasi, tetapi juga memunculkan bentuk kekerasan non-fisik yang dikenal sebagai kekerasan simbolik. Dalam konteks ini, perang komentar di media sosial menjadi salah satu manifestasi konflik digital yang sarat dengan ujaran kebencian, stigmatisasi, dan polarisasi opini. Sayangnya, kekerasan simbolik ini masih kurang mendapatkan perhatian dalam diskursus teologis maupun pendidikan agama Kristen kontemporer. Fenomena meningkatnya konflik verbal digital di kalangan peserta didik dan umat beragama menandakan adanya kekosongan etis yang perlu direspons secara teologis dan edukatif. Penelitian ini bertujuan untuk merumuskan dan mengkaji teologi perdamaian yang dapat diintegrasikan ke dalam Pendidikan Agama Kristen. Menggunakan metode kualitatif deskriptif dengan pendekatan analisi media sosial dan studi pustaka. Dapat disimpulkan bahwa pentingnya paradigma terkait hakikat kekerasan simbolik dalam perang komentar digital. Supaya prinsip-prinsip teologi perdamaian dalam nilai alkitabiah dapat diaktualisasikan dalam pendidikan agama Kristen sebagai instrumen etika perdamaian digital. dan tentunya sebagai formulasi kerangka etis teologi perdamaian untuk konteks pendidikan kristen digital. Pendidikan Agama Kristen memiliki potensi strategis sebagai sarana pembentukan karakter damai di era digital. Dengan demikian, kerangka etis ini diharapkan mampu memperkuat peran gereja dan sekolah dalam menciptakan budaya digital yang adil dan manusiawi.